Impulse oscillometry identifies peripheral airway dysfunction in children with adenosine deaminase deficiency. Issue 1 (December 2015) - Komarow, Hirsh; Sokolic, Robert; Hershfield, Michael; Kohn, Donald; Young, Michael; Metcalfe, Dean; Candotti, Fabio
Abstract Adenosine deaminase-deficient severe combined immunodeficiency (ADA-SCID) is characterized by impaired T-, B- and NK-cell function. Affected children, in addition to early onset of infections, manifest non-immunologic symptoms including pulmonary dysfunction likely attributable to elevated systemic adenosine levels. Lung disease assessment has primarily employed repetitive radiography and effort-dependent functional studies. Through impulse oscillometry (IOS), which is effort-independent, we prospectively obtained objective measures of lung dysfunction in 10 children with ADA-SCID. These results support the use of IOS in the identification and monitoring of lung function abnormalities in children with primary immunodeficiencies.